Studi Literature : Etika Teknologi Informasi Dalam Menghadapi Ancaman Malicious Insider - Dyah Ikhtiarti (Institute of Information Technology and Social Science (IITSS), 2020)
The development of information technology in Indonesia is experiencing rapid progress. One of them is that currently many companies and organizations operating in Indonesia use information technology and information systems in their business processes. One of the potential risks of attacks from within the company is known as insider threats. Therefore, service providers offer strong security policies and monitoring systems detect suspicious activities. The security models used are kill chain, network development life cycle (NDLC), convolutional neural network (CNN) and recurrent unit (GRU) as well as industrial control systems (ICS). The research results show that successful infrastructure security requires human resources, technical and policy aspects, how to implement advanced security technology that can prevent malicious insider crimes early on. Take proactive action to mitigate threats and protect systems from attacks and minimize potential losses. Keywords: Malicious Insiders, Insider Threats, Technology Information